Mathematical Belief Profile of Junior High School Students with Field Dependent Cognitive Style - Nurul Apriliani Balango; Pathuddin Pathuddin; Mubarik Mubarik; I Nyoman Murdiana (FKIP - Universitas Riau, 2026)
This study is motivated by the importance of students’ mathematical belief toward mathematical social norms in mathematics learning. Although research on mathematical belief and social norms has been widely conducted, studies specifically examining the mathematical belief of field dependent students remain limited. The purpose of this study is to describe the profile of mathematical belief of junior high school students with a field dependent cognitive style in the aspect of mathematical social norms. A descriptive qualitative approach was employed, with one student selected based on the Group Embedded Figures Test (GEFT) and the recommendation of a mathematics teacher. Data were collected through observation and semi- structured interviews, then analyzed using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. The findings show that the subject has a positive mathematical belief toward mathematical social norms, reflected in the ability to accept diverse levels of thinking, cooperate, actively ask questions, use symbols and rules accurately and consistently, and express ideas politely and systematically. These findings highlight the role of social interaction, collaboration, and mathematical communication in shaping the mathematical belief of field dependent students. Thus, their mathematical belief develops through active involvement in social interaction.